Estudo de revitalização dos blocos do campus UTFPR – Campo Mourão - Neves, João Vitor Ghidini (2016)
This project search through literature review and case studies, trying to create a alternative to the conceptual design inside UTFPR – Campo Mourão facilities changing the standard adopted in order to apply existing techniques in the market but are still little know and use by Brazilian engineers and architects seeking greater sustainability by the university as an institution and initiate discussion of why it is important the experience and practice of so-called “sustainable culture” for us users who are students, teachers, staff and visitors.